Awareness and Knowledge of Oral Cancer in Patients Visiting Nobel Medical College Teaching Hospital (Journal of Nobel Medical College, 2022)
Background: Oral cancer is one of the most common life-threatening conditions. Lack of awareness, knowledge, risk factors and early sign and symptom of oral cancer .Thus the aim of present study was to to evaluate the awareness and knowledge about oral cancer among patients.Materials and Methods: The descriptive cross-sectional study was done in Nobel Medical College Teaching Hospital, Biratnagar, Nepal from December 2020 to February 2021. Approval was acquired from Institutional Review Committee. A total of 300 patients above 25years of age group were included in the study. Self -administered questionnaire was prepared and distributed to obtain information about patient’s age, gender, education level and occupation. The questions regarded habits, awareness of oral cancer, knowledge of the risk factors, signs and symptoms and source of information about oral cancer.Results: A total of 300 patients participated in this study out of which male was 70%, and the female was 30%. The result of awareness questionnaire showed that 65% of the respondents were heard about oral cancer. The study revealed that 70.3% and 62.6% respectively patients were sable to correctly identify tobacco and smokeless tobacco as risk factor and 64% and 53.5% respectively was able to correctly identify white patch and red patch as signs and symptom of oral cancer. Majority of the respondent 46% yielded awareness and knowledge of oral cancer from media.Conclusion: The present study shows the dental patients had lack of awareness and knowledge about the risk factors and signs and symptom of oral cancer.